ANIES BASWEDAN'S POLITICAL COMMUNICATION STYLE ON INSTAGRAM - Sitompul, Elizabeth Vina; Anom, Erman (Jurnal Konseling Pendidikan Islam, 2024)
The purpose of this research is to examine Anies Baswedan's political communication style on Instagram. The research methodology utilized in this study is qualitative research, specifically a case study. The use of a case study is justified as it allows the researcher to gain an in-depth understanding of the context, processes, and complexities of the phenomenon under investigation. The research findings elucidate that Anies Baswedan, a prominent political figure in Indonesia, utilizes Instagram as a primary tool for communicating with his constituents. The analysis of Anies Baswedan's Instagram content, the use of hashtags and visual style, and the impact of his communication on voters and Indonesian politics are relevant and significant topics.